2017
DOI: 10.1177/0267658317717581
|View full text |Cite
|
Sign up to set email alerts
|

L1 Korean and L1 Mandarin L2 English learners’ acquisition of the count/mass distinction in English

Abstract: This study investigates the second language (L2) acquisition of the English count/mass distinction by speakers of Korean and Mandarin Chinese, with a focus on the semantics of atomicity. It is hypothesized that L1-Korean and L1-Mandarin L2-English learners are influenced by atomicity in the use of the count/mass morphosyntax in English. This hypothesis is tested in two experiments, one comparing Korean and Mandarin speakers in their L2 (English) and the other investigating count/mass morphosyntax in native Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 42 publications
5
31
1
Order By: Relevance
“…Kim (2005) argues that -tul directly encodes the distinction between object-denoting (atomic) nouns and substance-denoting (nonatomic) ones. This proposal has received experimental support from Choi, Ionin, and Zhu (2018), who examined the use and judgments of -tul by Korean native speakers. They found that -tul was optionally used, and optionally allowed, with all object-denoting nouns: both those that are count in English (e.g., chair) and those that are mass in English (e.g., furniture).…”
Section: Plural Marking Cross-linguistically and In L2 Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kim (2005) argues that -tul directly encodes the distinction between object-denoting (atomic) nouns and substance-denoting (nonatomic) ones. This proposal has received experimental support from Choi, Ionin, and Zhu (2018), who examined the use and judgments of -tul by Korean native speakers. They found that -tul was optionally used, and optionally allowed, with all object-denoting nouns: both those that are count in English (e.g., chair) and those that are mass in English (e.g., furniture).…”
Section: Plural Marking Cross-linguistically and In L2 Acquisitionmentioning
confidence: 99%
“…In contrast, -tul was both used and accepted to a much lower degree with substance-denoting nouns such as oil. Following Kim (2005), Choi et al (2018) conclude Korean -tul directly encodes atomicity. In contrast Mandarin -men, which is restricted to [human] nouns, does not encode atomicity; rather, atomicity has been argued to be reflected in the Mandarin classifier system (Cheng & Sybesma, 1998.…”
Section: Plural Marking Cross-linguistically and In L2 Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…All languages have specific positions for nouns and quantifiers that permit reference to objects in either the real or abstract world. The grammatical distinction of mass/count is encoded morphosyntactically and further connected to the conceptual/semantic distinction of object/substance (Choi, Ionin, & Zhu, 2017). The semantic component of the mass-count distinction is beyond the scope of this paper as the study focuses on the morphosyntactic aspects of this distinction.…”
Section: Introductionmentioning
confidence: 99%